Phosphorus adsorption characteristic of sediments in drainage ditch of paddy field in southern hilly tea field watershed - Yang Shaohui; Yang Jingping; Wang Hua; Zhao Xing (浙江大学学报. 农业与生命科学版, 2015)
Excess nutrients, especially phosphorus, running off from agricultural lands have contributed greatly to the eutrophication of water bodies in China. Drainage ditches are important conduits for drainage flows and unavoidably receive the discharge of nutrients, particulate matters, and other chemicals. Thus, more and more attention has been focused on the role of agricultural drainage ditch in water pollution control. However, few of the research were reported on drainage ditches of paddy field in southern hilly tea field watershed.In this paper, sediment samples collected from drainage ditch of paddy field in southern hilly tea field watershed were analyzed, according to the water discharging distance. The physico-chemical properties of sediments were determined and phosphorus isothermal experiments were also conducted.The result showed that water discharging distance had a significant influence on ditch soil properties. The concentrations of total phosphorus (TP) , oxalate-extractable ferric iron (Feox) , Alox and Pox increased with the discharging distance. The accumulation of P in the ditch soil was significantly correlated with total organic matters (TOM) and Alox, and the existence of TOM enhanced the activity of soil phosphorus. The degree of phosphorus saturation (DPSox) ranged from 1.50%-2.69%, much lower than the threshold value of P release. Both Langmuir equation and Freundlich equation could well describe the phosphorus adsorption behavior of ditch sediments, and the maximum P adsorption (Smax) ranged from 646.62 mg/kg to 754.17 mg/kg; Freundlich's adsorption constant (Kf) ranged from 271.81 L/kg to 338.74 L/kg. The sediments sampled from the end of the ditch had the maximum values of 338.74 L/kg and 754.17 mg/kg for Kf and Smax, respectively, which suggested that the sediment had the highest P adsorption capacity. The parameters calculated from the Freundlich and Langmuir isotherms ranged from 0.000 to 0.004 mg/L. In isothermal adsorption experiment, the adsorbed P amounts raised with the water discharging distance, but no significant differences were observed among P adsorption amounts of different ditch soils.In conclusion, for the studied ditch, sediment properties change as water discharging distance increasing, but not for P adsorption capacity. Besides, the sediments have large intrinsic P adsorption capacities and low risk of P release, which indicate that the ditch can be improved as ecological ditch to further P retaining.